2019
DOI: 10.1111/phn.12584
|View full text |Cite
|
Sign up to set email alerts
|

Roles of protective factors and risk factors in suicidal ideation among adolescents in Taiwan

Abstract: Objective To examine the role of protective factors and risk factors in suicidal ideation among adolescents in Taiwan based on a resilience protective model. Design and Sample A cross‐sectional design was employed. A total of 390 adolescents aged 15–19 years were recruited from four high schools in Taiwan by stratified random sampling. Methods An anonymous self‐report questionnaire was used to collect demographic characteristics, suicidal ideation, depressive symptoms, life stress, emotion‐focused coping, self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Life stress is associated with the onset of depression and suicide ideation; however, the ability to cope plays a mediating role. 109,110 People who have attempted suicide tend to have less useful coping strategies, such as avoidance. 111,112 Problemfocused active coping strategies, in contrast, may protect against suicidality.…”
Section: Ability To Cope With Stressmentioning
confidence: 99%
“…Life stress is associated with the onset of depression and suicide ideation; however, the ability to cope plays a mediating role. 109,110 People who have attempted suicide tend to have less useful coping strategies, such as avoidance. 111,112 Problemfocused active coping strategies, in contrast, may protect against suicidality.…”
Section: Ability To Cope With Stressmentioning
confidence: 99%
“…Several studies from different populations have shown that sleep problems are related to suicidal ideation [17,18]. Stressful life events are associated with increased suicidal ideation in adolescents [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Among the most critical risk factors for suicidal behaviors are physical and mental illnesses (13). More specifically, mood disorders (14) such as depression (15)(16)(17), and bipolar disorder (5) and others such as anxiety and psychological distress (16,(18)(19)(20), substance use disorders (21,22), borderline personality disorder (9), psychotic disorders (5) to name a few.…”
Section: Introductionmentioning
confidence: 99%